2017
DOI: 10.4049/jimmunol.1601045
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 Receptor Signaling Is Essential for TR1 Cell Function In Vivo

Abstract: Interleukin-10 (IL-10) is essential to maintain intestinal homeostasis. CD4+ T regulatory type 1 (TR1) cells produce large amounts of this cytokine and being therefore currently examined in clinical trials as T-cell therapy in patients with inflammatory bowel disease (IBD). However, factors and molecular signals sustaining TR1 cell regulatory activity still need to be identified in order to optimize the efficiency and to ensure the safety of these trials. We investigated the role of IL-10 signaling in mature T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 71 publications
7
90
1
1
Order By: Relevance
“…IL-10Rα signaling was shown to be dispensable for the differentiation of T R 1 T-cells, but not for the function of this cell type (46). Similarly, we investigated the effect of Il10Rb -/- on EOMES + PD-1 + CD4 + T-cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-10Rα signaling was shown to be dispensable for the differentiation of T R 1 T-cells, but not for the function of this cell type (46). Similarly, we investigated the effect of Il10Rb -/- on EOMES + PD-1 + CD4 + T-cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, IL-10 receptor expression is higher in EOMES-positive than -negative CD4 + T-cells, which is in accordance with data of CD8 + T-cells (53). Since IL-10-driven signaling via p38 MAPK was shown to be important to maintain IL-10 production in T R 1 CD4 + T-cells (46), we investigated the role of IL-10R signaling in CD4 + T-cells. Intriguingly, Il10rb -/- CD4 + T-cells showed a reduced CLL control alongside with a high expression of PD-1 as well as EOMES.…”
Section: Discussionmentioning
confidence: 99%
“…We further found evidence for changes in CD64+ populations in both the infected lung and colon. While IL-10 may directly regulate effector CD4 T cell function (35, 36), CD4 T cell differentiation and effector function may also occur due to altered myeloid function(s) (8, 10, 37, 38). Future studies using targeted disruption of IL-10 signaling in myeloid cells (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…have found that the damage degree of Tr1 cells is related to the clinical activity index scores of the disease.Moreover, scientists have also found that Breg cells can correct the Tr1 cell-related disorder, which is involved in IL-10, asPennati et al (2016) found in MS(Carter et al, 2012;Mielle et al, 2018).Previous studies have conducted in blood and intestinal tissue samples from mice and humans with IBD(Alfen et al, 2018;Brockmann et al, 2017). The researchers have found that Tr1 cells play an immunosuppressive role through IL-10 is related to p38 MAP kinase(Brockmann et al, 2017), and another important suppressive cytokine IFN-γ secreted by Tr1 cells can inhibit the transfer of colitis(Alfen et al, 2018). As for T1DM,Yu et al (2017) found that anti-CD3 mAb in the animal model can result in the alteration of gut microbiota and the increase of Tr1 cells(Yu, Paiva, & Flavell, 2018).…”
mentioning
confidence: 99%